Accelerating the selection process for Populus and Salix clones using short-term photosynthetic acclimation responses under greenhouse conditions. Issue 1 (3rd April 2017) - Mamashita, Takamitsu; Larocque, Guy R.; DesRochers, Annie; Beaulieu, Jean; Thomas, Barb R.; Mosseler, Alex; Major, John; Sidders, Derek
ABSTRACT: Leaf photosynthetic characteristics could be determinant factors to identify the most productive clones of hybrid poplars ( Populus spp.) and willows ( Salix spp.). Photosynthetic acclimation of hybrid poplars and willows was studied under greenhouse conditions. Seven Populus and five Salix clones were grown for 3 months at three spacings [20 × 20, 35 × 35, and 60 × 60 cm] and two nitrogen (N) levels (20 and 200 μg g −1 ). There were no significant spacing effects on leafless aboveground biomass per tree (AGBT) and height. Clonal acclimation to higher density was associated to increases in leaf area index (LAI) by 347% and specific leaf area (SLA) by 13% despite decreased leaf N content per unit leaf area (Narea ) by 31%. There were no changes in net CO2 assimilation rate ( A ) and photosynthetic N-use efficiency in the ambient light condition (PNUE amb ) within different spacings. The N addition alleviated competition effects by maximizing leaf area (LA) and SLA. Compared with less productive clones, more productive clones had 28% greater SLA, greater LA and AGBT per unit of increase in Narea over all treatments. The increased development of LA and SLA under high planting density is a key indicator of more productive clones.